Dielectric and Structural Properties of Poly(vinylidene fluoride) (PVDF) and Poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) Filled with Magnesium Oxide Nanofillers. (21st April 2019) - Arshad, A. N.; Wahid, M. H. M.; Rusop, M.; Majid, W. H. A.; Subban, R. H. Y.; Rozana, M. D.
Abstract : This study examines the dielectric properties of filled PVDF film and filled PVDF-TrFE film incorporated with 1, 3, 5, and 7 weight percentages of magnesium oxide (MgO) nanofillers. The metal-insulator-metal (MIM) configuration demonstrates PVDF/MgO with 7 weight percent of MgO which produced high dielectric constant (1 kHz) with low dielectric loss. The ATR-FTIR spectra of PVDF/MgO (7%) indicate wide bonding peaks at 840 cm -1 and 880 cm -1, assigned to -CH2 and -CF2 groups, respectively. This implies the presence of high content of β -crystals in the PVDF/MgO (7%) film. A shift in the peak was observed in the same film, from 1170 cm -1 to 1180 cm -1 suggesting possible transformation from γ -crystals to β -crystals. This film showed no apparent defect on its film surface. Thus, it established that PVDF incorporated with 7% MgO can be used to produce nanocomposite thin film for low-frequency electronic devices.